Permissive tolerance of the patent ductus arteriosus may increase the risk of Chronic Lung Disease - Kaempf JW; Huston R; Wu YX; Kaempf AJ; Wang L; Grunkemeier G; Mischel R; Cohen H; Freitag B (Dove Medical Press, 2013)
Joseph W Kaempf,1 Robert Huston,2 YingXing Wu,1 Andrew J Kaempf,1 Lian Wang,1 Gary Grunkemeier,1 Rebecca Mischel,2 Howard Cohen,3 Bret Freitag41Providence St Vincent Medical Center, Portland, OR, 2Randall Children’s Hospital at Legacy Emanuel, Portland, OR, 3Salem Hospital, Salem, OR, 4Legacy Salmon Creek Hospital, Vancouver, WA, USAPurpose: Because early closure therapies of the patent ductus arteriosus (PDA) have not been shown to confer benefit to premature infants, the authors’ four neonatal intensive care units adopted a less aggressive PDA management protocol.Study design: A before–after investigation in infants with PDAs born 501–1500 g. Era 1 (January 2005 to December 2007) featured traditional management with indomethacin and/or surgical ligation used early to close PDAs; Era 2 (January 2008 to June 2009) featured fluid restriction and watchful waiting for PDA closure, limiting indomethacin or surgical ligation to only those infants with large PDAs needing significant respiratory support.Results: Era 2 infants (n = 129, mean ± standard deviation 27 ± 2 weeks) received less and later indomethacin and less Day 1–28 total fluids as compared to Era 1 infants (n = 240, mean ± standard deviation 27 ± 2 weeks). The Chronic Lung Disease (CLD) rate was higher in Era 2 (48% versus 34%, P < 0.01) as was the combined outcome of Death after Day 7 or CLD (57% versus 42%, P < 0.01). Multiple regression analysis showed Era 2 birth was a predictor of CLD. However, Poisson regression analysis determined the predictors of all seven major Vermont Oxford Network morbidities were earlier gestational age, lower birth weight, and male gender, not the era of birth. Significantly more infants were discharged home with PDAs in Era 2.Conclusion: Permissive tolerance of PDAs may increase the risk of CLD and Death after Day 7 or CLD but is not associated with significant changes in other Vermont Oxford Network morbidities.Keywords: premature infant, indomethacin, surgical ligation, quality improvement